Peran Strategis Kepemimpinan Transformasi Dalam Implementasi Harvest Theology Untuk Pertumbuhan Gereja di Era Postmodern - Burton, Ray; Silalahi, Frans H. M. (Syntax Corporation, 2026)
One of the important aspects of the church as a community of followers of Jesus Christ in this world is the growth of the congregation in quantity and quality. The Church as an organization must carry out various well-planned actions under the leadership of its servants and activists to achieve this goal. One part of theology called Harvest Theology focuses on how the followers of Christ should harvest the fields that have turned yellow so that the souls are brought to Christ to receive the salvation He has promised for all people. To make all followers of Christ reapers, transformational leadership is needed that can create a vision and carry it out with all its members. To demonstrate the role of transformational leadership in the implementation of Harvest Theology, this study uses a qualitative method. This study will show how important it is for church leaders who have transformational leadership to transform their members to achieve the Lord's purpose to make all people His disciples. This process of transformation is very important to be done well in every church because it is for this purpose that God calls everyone to be a witness of Christ in a world corrupted by evil. Transformational leaders are needed by the church to make changes that are recognized and followed by its members.